Creative Industry and Women Writers as Labor in the Platform Economy - Zulfa Ruhama; Ary Nilandari (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2023)
Starting from non-commercial, user-generated content, grassroots alternative to the industry-controlled major publishers, web-novel writing in Indonesia has formalized business model and grown bigger with the influx of capital. Very little is known about the mutually shaping relationship of the online creative writing market in Indonesia for women in the wider context of the creative labor debate. This paper will analyze the inception of online writing jobs in Indonesia, before probing the formalization process, taking into account all the associated precarity of informal labor. It then looks into its economic and socio-cultural implications, such as the impact on the formal market and how it can improve employment conditions for creative labor. The findings suggest that writing in the platform economy is typecast as women jobs, with many web novel platforms marketing strategies caters to women audiences. Its further growth and expansion will lead to the empowerment and employment of more women in the platform economy. However, women writer working in platform economy in Indonesia are very vulnerable, with most of them occupying the middle-low payment jobs that require complex skills. The proper regulation establishment from government and education about basic employee rights can improve employment conditions for women writers in platform economy.